Perancangan Aplikasi Persediaan Barang Berbasis Web Dengan Menggunakan Metode Rational Unified Process (RUP) (Studi Kasus : UD Aman Jaya 03) - Mukti Rizky, Kusdiana; Mulyana, Dadan; Sidiq, Maulana (Jurnal Mahasiswa Sistem Informasi Galuh, 2025)
In the era of ever-growing digitalization, the use of computer media and systems has become a priority to improve company performance. Manual processes previously carried out by companies can now be replaced by computers which offer more effective and efficient data processing and support management decision making. However, there are still many companies that are not computerized properly due to a lack of human resources (HR) who understand computerized systems. UD Aman Jaya 03, a timber company operating in the trading sector, is facing problems in recording incoming and outgoing goods which are still done manually. This causes frequent data loss, delays in inventory preparation, and slow and inaccurate data processing. To overcome this problem, the author designed a web-based inventory information system application using the Rational Unified Process (RUP) method. With this computerized system, recording of incoming and outgoing goods can be done quickly and accurately, thereby increasing the efficiency and effectiveness of data processing in the company.